Організація навчання дорослих у Великій Британії на основі емпіричних моделей - Орос Ільдіко; Orosz Ildikó; Oros Ildiko (СумДПУ імені А. С. Макаренка, 2018)
Резюме. У статті розглянуто моделі навчання, що застосуються в практиці додаткової освіти дорослих у Великій Британії – традиційно-дидактична модель навчання; проблемно-пошукова модель навчання, циклічна чотириступінчаста емпірична модель процесу навчання, андрагогічна модель навчального процесу англійського дослідника П. Джарвіса. Доведено, що в останні роки основну позицію в науковому обґрунтуванні додаткової освіти дорослих займають емпіричні теорії навчання, які центральним концептом своїх педагогічних систем вважають досвід учнів.

Abstract. Data obtained by foreign researchers indicate the possibility of successful organization of the educational process with adult population. Foreign andragogy scholars have suggested pedagogical models of adult learning using experience. The article examines teaching patterns used in the practice of adult education in the UK. The traditional didactic model of education is based on the stereotyped understanding of learning, in which the teacher communicates knowledge, skills and values to adult students with a subsequent assessment of their learning. In the process of problem-searching model of teaching, the Andragog teacher asks adults questions and gives them the opportunity to exploit, that is, consciously formulate the knowledge that exists in adults implicitly and they themselves formulate them, using their own experience, taking active part in the learning process. Scientists D. Colb and R. Fry have developed a model for adult learning, which reflects the stages of assimilating specific experiences - a cyclic four-step empirical model of the learning process. Scientist B. Barnett offered the training cycle "Model of Reflexive Thought and Action", adding to four components of the model of D. Colb - Empirical cycle of training - the fifth component - planning for implementation. In the UK, adult English education is widely used by the English researcher P. Jarvis and the logical model of the educational process. This model of empirical learning is of greatest importance to science and practice, because it covers all possible human acquisitions of new experiences both in teaching and in a social situation; directs the actions of the andragogue to improve management of the learning process.
Organization of adult education in the Great Britain based on empirical models
http://nbuv.gov.ua/UJRN/pednauk_2018_10_28
Keywords: організація навчання дорослих; Велика Британія; емпіричні моделі; освіта дорослих; практика додаткової освіти дорослих; organization of adult education; Great Britain; empirical models; adult education; practice of adult education